Rancangan Sistem Monitoring Penyimpanan Beras Menggunakan IoT Berbasis Website - Ida Bagus Satrya Masyana Citarsa; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
With the current technological advancements, there has been significant progress in monitoring systems, one of which is the rice storage monitoring system. Monitoring systems that were previously manual can now be automated and more efficient using IoT technology. This system is designed to monitor the temperature, air humidity, and air quality in rice storage facilities. IoT devices that can be used to design this system include NodeMCU ESP 8266, DHT 11 sensor and MQ-2 sensor. Additionally, a server and website are required for monitoring purposes. By utilizing NodeMCU ESP8266, which can connect to a Wi-Fi network, data from the sensors can be monitored online through a website. The design of this system employs the Research and Development method commonly used for product development. The aim of this system design is to simplify the monitoring of rice storage facilities for increased efficiency.